Study of Spray System Applications of Edible Coating Suspensions Based on Hydrocolloids Containing Cellulose Nanofibers on Grape Surface (Vitis Vinifera L.) - Vega-Viveros, R; Osorio-Lira, F; Zamorano-Riquelme, M; Silva-Weiss, A; Silva-Vera, W; Gimenez-Castillo, B (Springer New York LLC, 2018)
An edible coating is a useful technology to preserve fruit quality by covering them with a protective layer which improves the appearance and provides a semipermeable barrier for gases and water vapor transfer, allowing extension of their shelf life. In this study, edible coatings based on hydroxypropyl methyl cellulose, k-carrageenan, glycerol, and cellulose nanofibers were formulated. The operational conditions of the spray system were studied to obtain a coating with optimal adhesion on grape (Vitis vinifera L.) surface. Furthermore, the physico-chemical properties of grapes covered with edible coatings were evaluated during refrigerated storage. A full factorial 23 experimental design was applied, where liquid suspension flow (1-5 L h-1), air pressure (50-200 kPa), and height of impact (0.3-0.5 m) were evaluated as independent variables, whereas the percentage of coating and thickness of coating was the response variables. Both mechanical and physico-chemical properties were evaluated during 41 days in both coated and uncoated grapes as shelf life criteria. Throughout the storage time, noticeable changes in pH and total soluble solids were not found in grapes covered with edible coatings and they showed the highest stability for the evaluated mechanical properties. Moreover, coated grapes showed final weight loss and water vapor permeability values of approximately 30 and 34% lower, respectively, than uncoated grapes, suggesting a shelf life extension. © Springer Science+Business Media, LLC, part of Springer Nature 2018.